Decreased Glial GABA and Tonic Inhibition in Cerebellum of Mouse Model for Attention-Deficit/Hyperactivity Disorder (ADHD) - Kim, Yoo Sung; Woo, Junsung; Lee, C. Justin; Yoon, Bo-Eun (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2017)
About 5 similar to 12% of school-aged children suffer from the Attention-Deficit/Hyperactivity Disorder (ADHD). However, the core mechanism of ADHD remains unclear. G protein-coupled receptor kinase-interacting protein-1 (GIT1) has recently been reported to be associated with ADHD in human and the genetic deletion of GIT1 result in ADHD-like behaviors in mice. Mice lacking GIT1 shows a shift in neuronal excitation/inhibition (E/I) balance. However, the pricise mechanism for E/I imbalance and the role of neuron-glia interaction in GIT1 knockout (KO) mice have not been studied. Especially, a possible contribution of glial GABA and tonic inhibition mediated by astrocytic GABA release in the mouse model for ADHD remains unexplored. Therefore, we investigated the changes in the amount of GABA and degree of tonic inhibition in GIT1 KO mice. We observed a decreased glial GABA intensity in GIT1 KO mice compared to wild type (WT) mice and an attenuation of tonic current from cerebellar granule cells in GIT1 KO mice. Our study identifies the previously unknown mechanism of reduced astrocytic GABA and tonic inhibition in GIT1 lacking mice as a potential cause of hyperactivity disorder.
Keywords: DEFICIT HYPERACTIVITY DISORDER; BRAIN-DEVELOPMENT; ANIMAL-MODELS; BASAL GANGLIA; MOTOR; MICE